2003
DOI: 10.1016/s0013-7944(02)00097-8
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic plasticity at pores and inclusions in cast Al–Si alloys

Abstract: Finite element analyses of micronotches including pores and silicon particles of an A356 aluminum alloy were performed to elucidate microstructure-property relations for fatigue crack incubation. Several important findings resulted. By varying the particle and pore size, spacing, aspect ratio, and clustering, the relative microstructural differences were quantified related to micronotch root cyclic plasticity. Results from realistic two-dimensional microstructures showed that minimal microstructure-scale cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 17 publications
4
96
1
Order By: Relevance
“…This was the case for the gravity sand cast material investigated by Koutiri et al [12,13] for which it was found that the final failure was typically caused by fatigue cracks that originated from large micro-shrinkage pores. Conversely, for a very similar material treated by the HIP post-casting process, so that micro-shrinkage porosity is dramatically reduced, the fatigue strength is controlled by the first fatigue damage mechanism [32] (see Figure 11). …”
Section: Cast Aluminium Alloysmentioning
confidence: 99%
“…This was the case for the gravity sand cast material investigated by Koutiri et al [12,13] for which it was found that the final failure was typically caused by fatigue cracks that originated from large micro-shrinkage pores. Conversely, for a very similar material treated by the HIP post-casting process, so that micro-shrinkage porosity is dramatically reduced, the fatigue strength is controlled by the first fatigue damage mechanism [32] (see Figure 11). …”
Section: Cast Aluminium Alloysmentioning
confidence: 99%
“…Much research has been reported in the scientific literature concerning the fatigue behaviour of cast aluminium-silicon alloys [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17] and [18]. This body of work is generally related to uniaxial loads at low R-ratios (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…silicon particles in the eutectic zones, intermetallic phases or oxides) [6], [4] and [5]. The concept of elastic shakedown at the mesoscopic scale is then sometimes used to evaluate the fatigue life, as per certain multiaxial fatigue criteria like the Dang Van[1], [19] and [20], Papadopoulos [21] or the Huyen and…”
Section: Introductionmentioning
confidence: 99%
“…The shear friction driving model was used for the friction between the contact surfaces of the billet and the die. All of the initial parameters in numerical simulation are shown in Table 1 [9][10][11][12].…”
Section: Numerical Simulation Of Continuous Extrusion and Rollingmentioning
confidence: 99%